The effect of shopping channel (online vs offline) on consumer decision process and firm's marketing strategy - Xu, Cheng; Park, Jooyoung; Lee, Jacob C (Internet research, 2022)
PurposeThis research investigates the novel questions of whether and how specific forms of shopping channels (online vs offline) influence consumers' decision-making. Moreover, this research investigates marketing firms' proper marketing strategies across different shipping channels.Design/methodology/approachThe authors conducted three studies using a large sample (N = 703) recruited from a diverse pool (students and adults) that examined multiple products (camera and car) across different shopping channels (online vs offline). Study 1a (n = 251) and Study 1b (n = 252) examined the effect of an online versus offline channel on consumers' decision-making using a one-factor (shopping channel: online vs offline) between-subjects design. Meanwhile, Study 2 (n = 200) investigated the effective strategies that firms should employ across different shopping channels using a 2 (shopping channel: online vs offline) × 2 (mental simulation: outcome vs process) between-subjects design. Participants in the online condition evaluated the product on a computer screen, whereas participants in the offline condition evaluated the real product assuming a real-world retail store setting.FindingsThe three studies supported the predictions that shopping channels (online vs offline) affect consumers' psychological distance and, in turn, affect their decision process. Specifically, results reveal that the online (offline) channel increases (decreases) psychological distance and leads consumers to pay more attention to a product's desirability (feasibility) aspects.Originality/valueGiven that many firms sell the same products through multiple channels, the findings of this research offer insightful theoretical and practical implications.